CORE DESIGN OF TRIGA2000 BANDUNG USING U3Si2/Al FUEL ELEMENT MTR TYPE - Pinem, Surian; Surbakti, Tukiran; Sembiring, Tagor Malem (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The TRIGA2000 Bandung reactor currently uses cylinders fuel type, but the fuel production has been discontinued. In order to operate continuously, it is planned that the TRIGA2000 reactor should change the fuel from cylinder type to U3Si2/Al MTR type since Indonesia has been able to produce such fuel element. In this research calculation of TRIGA2000 coreusing U3Si2/Al fuel MTR type of three different fuel densities has been done. This activity begins with performing neutron macroscopic cross section generation for all core materials as a function of temperature, burn up and xenon. The cross-section generation was performed with the WIMSD5 code. The calculation of the core parameters were done with the Batan-FUEL code. Based on the calculation of neutronic parameters, there are three core configurations, i.e.core with 16 fuel elements and 4 control elements (Core 16/4), core with 14 fuel elements and 4 control elements (Core 14/4) and core with 12 fuel elements and 4 control elements (Core 12/4). The three cores meet the safety constraint but only the Core 16/4 that uses U3Si2/Al fuel with a density of 2.96 gU/cm3. The maximum thermal neutron flux in the core center is 5.874×1013 n/cm2s with core cycle length is 245 days at 2 MW. The results show that the TRIGA2000 core can be converted from cylinder type fuel to silicide MTR type.